Circular Economy Elements in Marketing Communications: An Opinion Perspective for a Sustainable Future - Ravichandran, Sabari Shankar (Prabandhan: Indian Journal of Management, 2023)
Purpose : This research aimed to explore the role of the circular economy (CE) in shaping contemporary marketing strategies and promoting sustainable consumption among consumers. The study aimed to delve into the complexities involved in driving behavioral changes toward circular consumption and how marketers can transcend traditional rational marketing communications to achieve this goal. Methodology : This research adopted an opinion perspective based on a thorough review of literature from credible sources. It drew on research papers published in high-quality peer-reviewed journals focusing on circular economy, sustainability, and marketing communications. Key Findings : The study examined the application of the elaboration likelihood model to understand how marketers can effectively persuade and influence consumer behavior for a sustainable future. It sheds light on marketers’ utilization of the central route and peripheral route strategies to incorporate circular economy principles. Practical Implications : The insights presented in this research offered valuable guidance to policymakers and marketers in promoting sustainable thinking among consumers and encouraging circular consumption patterns. Consequently, the findings contributed not only to the well-being of consumers and societies in terms of sustainability but also aligned with the United Nations Sustainable Development Goals (UNSDGs) for the year 2030. Originality : The significance of circular economy and sustainability in the marketing landscape is gaining prominence. This research stands out by offering novel insights and opening up new avenues for further exploration in both theoretical and practical aspects, aspects that have been relatively underexplored in existing literature and practice.